Effect of interfacial layers on physical and electrical properties of dinaphtho[2, 3-b:2′, 3′-d]thiophene organic thin-film transistors. (24th January 2017) - Shaari, Safizan; Naka, Shigeki; Okada, Hiroyuki
Abstract: We fabricated hexyl-substituted dinaphtho[2, 3- b :2′, 3′- d ]thiophene (C6-DNT-V) organic thin-film transistors (OTFTs) with different interfacial layers. The interfacial layers comprised various types of polymers, polyimide, self-assembled monolayers, and high-κ materials. We investigated the effect of interfacial layers on the physical and electrical properties of C6-DNT-V OTFTs. The relationships between mobility and contact angle, threshold voltage and contact angle, on/off ratio and contact angle, mobility and X-ray diffraction intensity, and mobility and dielectric constant were investigated. We found that the contact angle strongly affected the threshold voltage, and the correlation coefficient was calculated to be 0.88. This is due to the fact that use of interfacial layers on the dielectric surface changes the contact angle and hence the surface energy. The altered surface energy will contribute to a change in the grain boundary of C6-DNT-V and affect the shift in threshold voltage. The relationships between other properties showed correlation coefficients of lower than 0.51.